Experimental study of dynamic shear stiffness decay characteristics of interbedded soil: a case study in Yangtze River floodplain - Liu, Haizhi; Huo, Zhilei; Chen, Danxi; Zhou, Ruirong; Wu, Qi (Frontiers in Earth Science, 2024)
To explore the characteristics of the dynamic shear modulus of river-phase (as opposed to estuarine) floodplain interbedded soil, undisturbed interbedded soil from the floodplain of the Yangtze River in Nanjing was subjected to strain-controlled cyclic triaxial tests to investigate how the initial effective confining pressure (σʹm), consolidation ratio (kc), and degree of consolidation (U) influence the maximum dynamic shear modulus Gmax and the dynamic shear modulus ratio G/Gmax. The results show that for this soil, G decreases with increasing strain amplitude, and for a given strain amplitude, G increases with increasing σʹm, kc, and U. Compared with soil from the Yangtze estuary, kc has a greater effect on Gmax of the floodplain interbedded soil. Finally, a modified Martin-Davidenkov model is proposed for predicting G/Gmax of river-phase floodplain interbedded soil under different σʹm, kc, and U.